Management of Cerebral Palsy: A Literature Review from a Physiatric Perspective (TAJ: Journal of Teachers Association, 2011)
To examine the literature on cerebral palsy (CP), as it is related to rehabilitation treatment and exercises, more than 40 articles related to CP were selected from different national and international journals and then it was reviewed. Cerebral Palsy is a disabling disease of the children and this condition is life long for that child. So rehabilitative measurement is necessary for proper daily living activities of the patient with CP. There is improvement of the condition with the help of some medicines, physical therapy, braces, strength training and surgery. But this review points out the need for more carefully designed studies of CP to see the beneficial effects of rehabilitation measures. DOI: http://dx.doi.org/10.3329/taj.v14i2.8399 TAJ 2001; 14(2): 104-107